Da experiência não autêntica à busca por vivências humanizadoras: a prática curricular freireana em ciências - Gomes, Carla Garcia de Santana (2014)
Based on the concepts of experience and Walter Benjamin's living, the present study aims to construct and investigate a proposed curriculum in sciences based on the pedagogy of Paulo Freire, aiming at the possibility of providing humanizing experiences, which in the context of the classroom, are able to contribute to a education greater social quality and to overcoming some difficulties related to science teaching. For this purpose, from a qualitative methodological approach, identified with the theory of action research, were conducted participating observations and constructed a plan of action, that constituted himself in a programmatic sequence for science teaching in the context of a public school the municipal education of Sao Paulo. This sequence had how theoretical and methodological referentials: the process of thematic research via generator theme as proposed by Paulo Freire, the thematic network by Antonio Gouvêa da Silva, and the three pedagogical moments influenced by Freire's pedagogy and suggested by Demétrio Delizoicov, José Angotti and Marta Pernambuco. Data obtained during this process constitute in the students' productions, collected and organized for later analysis, and records kept by the teacher-researcher in the field diary. The analysis of the data was under the light of freirean thinking and in benjaminianos concepts of experience. The curricular experience made possible positive changes, in ethical and critical perspective, in the form of learners interpret and position themselves through social reality which points to the possibility of humanizing experiences through a freirean curricular practice. And while promoting contextualized practices, dialogical, problematizing and participatory practices showed possible advances in overcoming some of the difficulties encountered nowadays in science teaching.